Isolation of Infectious Bronchitis Virus from an Outbreak in Parent Layer Stock - Naik, B.M. Chandra; Santhosh, S.R.; Sridhar, B.Y.; Mayanna, Asha; Gomes, Amitha R.; Harish, B.R.; Mamatha, G.S.; Jayakumar, S.R.; Krishnappa, G. (International Journal of Poultry Science, 2005)
Trachea and lung tissue samples collected from a disease outbreak at Regional Poultry Farm, Kerala, India were submitted for virological investigation at Institute of Animal Health and Veterinary Biologicals (IAH & VB), Bangalore. The outbreak had taken a toll of 385 layer parent stock birds. The main symptoms and lesions were air saculitis, tracheal rales, oopheritis and salphingitis. The samples were processed and inoculated to 10th day old chicken embryos. Lesions of dwarfing and curling characteristic of Infectious bronchitis were noticed in inoculated embryos. The virus was confirmed by a modified Haemagglutination (HA) test, wherein the allontoic fluid was pretreated with crude filtrate of Clostridium perfringens before carrying out HA.